Analisis Derajat Status Kesehatan pada Pekerja Tukang Kayu di Tempat Kerja PT. XYZ Balikpapan - Reny Widyanatasari; Lina Yuliana; Iwan Zulfikar (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2022)
As efforts to implement occupational health include preventive, promotive, curative and rehabilitative health/medical efforts. Thus, occupational health is one of the two main pillars of progress and cleanliness of Occupational Health and Safety. The health examination of the workforce aims to improve and maintain the degree of physical, mental and social health. Carpenter is someone who has the task of assembling and installing scaffolding, formwork, roof trusses, stairs, railings, floor construction, wooden walls, and installing window door frames, ceiling frames and ceiling coverings based on working drawings, technical specifications and work instructions. . The purpose of the study was to determine the relationship between the degree of health status of Carpenter. This type of research was an analytic survey with a cross sectional study approach. This research was conducted from June to September 2021. The population was 105 people and a sample of 52 people was determined by the purposive sampling method. Data collection techniques by means of interviews and document review. The tools for data collection are questionnaires and Medical Check Up results, for in-depth interviews conducted to HSE officers. The results of this study indicate that there is no relationship between the work area (0.692) and the health status of carpenter workers. Based on the results of the study, it can be concluded that there is no relationship between the work area and the degree of health status of Carpenter workers at PT. XYZ Balikpapan.